Economy and planet: a blind spot for community psychology? - Burton, Mark; Steady State Manchester and Manchester Metropolitan University. (2016)
Conventional economics shares a number of characteristics with mainstream psychology: individualism, acontextualism, and both social and ecological irrelevance. Community psychology has been one response to the shortcomings of mainstream psychology, but has not typically engaged with criticisms of the conventional economics with which it shares assumptions, nor with the economic dimension of community. I reflect on experience promoting alternatives to the dominant economic growth / global competitiveness policy paradigm in the region of Manchester, England, and on the community psychological nature of this project. Community psychology can help articulate an alternative set of values and provide conceptual and practical tools for counter-hegemonic social movements, but the path from community psychology praxis to social movement praxis is not obvious